ATAXIN-2 activates PERIOD translation to sustain circadian rhythms in Drosophila. - Lim, C.; Allada, R. (Science, 2013)
Evidence for transcriptional feedback in circadian timekeeping is abundant, yet little is known about the mechanisms underlying translational control. We found that ATAXIN-2 (ATX2), an RNA-associated protein involved in neurodegenerative disease, is a translational activator of the rate-limiting clock component PERIOD (PER) in Drosophila. ATX2 specifically interacted with TWENTY-FOUR (TYF), an activator of PER translation. RNA interference-mediated depletion of Atx2 or the expression of a mutant ATX2 protein that does not associate with polyadenylate-binding protein (PABP) suppressed behavioral rhythms and decreased abundance of PER. Although ATX2 can repress translation, depletion of Atx2 from Drosophila S2 cells inhibited translational activation by RNA-tethered TYF and disrupted the association between TYF and PABP. Thus, ATX2 coordinates an active translation complex important for PER expression and circadian rhythms.